Association Between Brain Atrophy with EDSS and Number of Lesion Sites in Indonesian Multiple Sclerosis Patients - Estiasari, Riwanti; Firdausia, Salsabila; Mulyadi, Rahmad; Yunus, Reyhan Eddy; Maharani, Kartika; Imran, Darma (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction : Multiple sclerosis (MS) is a potentially disabling inflammatory demyelination of the central nervous system. The demyelination process will end up with the destruction of neurons that leads to the decrease of brain volume. Brain atrophy may cause more severe disability and affect the quality of life of MS patients, who are mostly at a young age. Objective : Our study aims to assess the brain atrophy among Indonesian MS patients and the association between with the degree of disability. Material and methods : A cross-sectional study included 28 MS patients. To determine the brain atrophy, we compared 11 healthy control group to the MS group. Head MRI was performed using 1.5T MRI and the brain volume was processed with Freesurfer type 6.0 automatic software. Result : The white matter (WM) and gray matter (GM) volume of MS patients was significantly lower compared to normal control with 78.6% GM atrophy and 67.9% WM atrophy. EDSS score is significantly associated with WM atrophy but not with GM atrophy. Factors related to WM atrophy is age, age of onset, and subtype of MS. A number of lesion sites were found greater in subjects with GM and WM atrophy. Discussion : The mechanisms of brain atrophy in MS involve inflammatory processes and neurodegeneration. Various factors, including lesion volume impact atrophy rates. Brain atrophy had correlation with EDSS scores. Conclusion : Brain atrophy was common in MS patients and significantly associated with the level of disability and number of lesion sites.